Recursive natural join operation in bitemporal nested relations. (1st January 2013) - Garani, Georgia
The natural join operation for bitemporal attribute timestamping nested relations of arbitrary depth is formally defined. The advantages of nesting, recursion, and attribute timestamping are combined. Different cases of the operation are distinguished, relevant to the number, the type and the nesting levels of the common attributes involved. An algorithm is presented for the generalised case. The natural join operation is proved to be a consistent extension of the natural join operation of the conventional relational model. The notion of the temporal nested key is redefined.